Estudio geológico de suelos en el sector Vinchoa de la parroquia Veintimilla del cantón Guaranda - Poma Taris, Jorge Luis (2018)
The project realized at Veintimilla’s Parish in Guaranda canton consisted in the geological study of soils, based on the characterization of soils from the geological point of view, it also analyzes their physical, geological and morphological characteristics.Gauges were made in order to identify soil types, with a depth of 1.5 m, identifying three types of soil horizons. Samples were obtained with a pH of 6.18 considered as acid soils due to the scarcity of forests.As a reference in Vinchoa, the soil of one of the communities has the following percentages: sand content 62,8 %, sludge 36,0% and clay 1,2%, density 2.24 g / cm3.The analyzed soils would meet the speci c requirements of suitable soil for agricultural use and buildings. e morphology of the area is characterized by not very steep slopes, predominating slopes in the order of 5% to 70%.